Citizen Science Book Resources - Silka, Linda (Maine Policy Review, 2017)
Linda Silka briefly reviews The Rightful Place of Science: Citizen Science, edited by Darlene Cavalier and Eric B. Kennedy; Citizen Science for All: A Guide for Citizen Science Practitioners; Citizen Science: How Ordinary People Are Changing the Face of Discovery by Caren Cooper; Citizen Scientist: Searching for Heroes and Hope in an Age of Extinction by Mary Ellen Hannibal; Lewis & Clark: Pioneering Naturalists by Paul R. Cutright; and Braiding Sweetgrass by Robin Wall Kimmerer